Direct Targeting of the mTOR (Mammalian Target of Rapamycin) Kinase Improves Endothelial Permeability in Drug-Eluting Stents—Brief Report. Issue 9 (September 2018) - Harari, Emanuel; Guo, Liang; Smith, Samantha L.; Paek, Ka Hyun; Fernandez, Raquel; Sakamoto, Atsushi; Mori, Hiroyoshi; Kutyna, Matthew D.; Habib, Anwer; Torii, Sho; Cornelissen, Anne; Jinnouchi, Hiroyuki; et al.
Abstract : Objective—: Drug-eluting stents eluting canonical mTOR (mammalian target of rapamycin) inhibitors are widely used to treat coronary artery disease but accelerate the development of atherosclerosis within the stent (neoatherosclerosis)—a leading cause of late stent failure. We recently showed that canonical mTOR inhibitors bind FKBP12.6 (12.6-kDa FK506–binding protein 12), displace it from calcium release channels, resulting in activation of PKCα (protein kinase Cα) and dissociation of p-120-catenin (p120) from VE-CAD (vascular endothelial cadherin; promoting endothelial barrier dysfunction [EBD]). However, the relevance of these findings to drug-eluting stents remains unknown. Newer generation direct mTOR kinase inhibitors do not bind FKBP12.6 and offer the potential of improving endothelial barrier function while maintaining antirestenotic efficacy, but their actual effects are unknown. We examined the effects of 2 different pharmacological targeting strategies—canonical mTOR inhibitor everolimus and mTOR kinase inhibitors Torin-2—on EBD after stenting. Approach and Results—: Using the rabbit model of stenting and a combination of Evans blue dye, confocal and scanning electron microscopy studies, everolimus-eluting stents resulted in long-term EBD compared with bare metal stents. EBD was mitigated by using stents that eluted mTOR kinase inhibitors (Torin-2–eluting stent). At 60 days after stent placement, everolimus-eluting stents demonstrated large areas of Evans blue dye staining and evidence of p120 VE-CAD dissociation consistent with EBD. These findings were absent in bare metal stents and significantly attenuated in Torin-2–eluting stent. As proof of concept of the role of EBD in neoatherosclerosis, 100 days after stenting, animals were fed an enriched cholesterol diet for an additional 30 days. Everolimus-eluting stents demonstrated significantly more macrophage infiltration (consistent with neoatherosclerosis) compared with both bare metal stents and Torin-2–eluting stent. Conclusions—: Our results pinpoint interactions between FKBP12.6 and canonical mTOR inhibitors as a major cause of vascular permeability and neoatherosclerosis, which can be overcome by using mTOR kinase inhibitors. Our study suggests further refinement of molecular targeting of the mTOR complex may be a promising strategy (Graphic Abstract). Abstract : Supplemental Digital Content is available in the text.